Answer:
Step-by-step explanation:
6x - 5y = 15....... (1)
x=y+3..........(2)
Putting (2) in (1)
6(y + 3) - 5y = 15
6y + 18 - 5y = 15
6y - 5y = 15 - 18
y = -3
And x = y + 3
x = -3 + 3
x = 0
The formula for the light bend would be n1*sin i= n2 * sin r
If you use "sin (90-x)= cos x" principle, you can change the sin in the equation into
n1*sin i= n2 * sin r
n1 * cos a= n2 * cos b
n2/n1= cos a/ cos b
Assuming the n constant is the ratio of the glass compared to water then the answer would be: cos a/ cos b
Answer: Addition and subtraction is performed after multiplication, division and remainder
Step-by-step explanation:
The correct order of operations is to calculate whatever is in the parenthesis first.
Then calculate multiplication and division depending on which comes first as you move from left to right.
Then addition and subtraction can be performed also depending on which comes first as you move left to right.
Answer:
by 12 cause 6×12 is 72 so if you multiply the whole thing by 12 it would be equal to 24/72
3.60 / 60cm = .06/cm or 6 cents per centimeter
100cm = 1m
$.06 * 100cm = $6.00 / m
100m = 100 * $6.00
= $600